Body Mass Index and Medical Expenses Covered by the National Health Insurance Service in Korean Adults - Youn Huh; Ga Eun Nam; Hye Soon Park (Journal of Obesity & Metabolic Syndrome)
Background : This study aimed to analyze the medical expenses covered by the Korean National Health Insurance Service (KNHIS) according to body mass index (BMI) in Korean adults. Methods : We included 1,170,464 adults (623,498 men and 546,966 women) aged ≥19 years from the KNHIS-National Sample Cohort database (2016 to 2019) after excluding individuals with cancer. Average annual medical expenses per person and average annual medical expenses (Korean won [KRW], 1 United States dollar= 1,292 KRW) by BMI classification were assessed according to age and sex. Medical expenses comprised those for medication and combined outpatient department (OPD) and hospitalization services. Means and 95% confidence intervals were analyzed using a two-part model. Results : Average annual medical expenses increased in higher BMI quintile groups (P for trend <0.001). Average annual medical expenses per person increased significantly as BMI increased in women but not in men. Average annual medical expenses were highest in the highest quintile of BMI among women and in all age groups. While BMI showed a U-shape association with medical expenses for OPD and hospitalization in young individuals, medical expenses for medication in all age groups and those for OPD and hospitalization in middle-aged individuals increased sharply in the highest BMI quintile. Conclusion : All types of average annual medical expenses increased in higher BMI groups in Korean adults, particularly in women. Individuals with the highest BMI quintile incurred the greatest medical expenses among women and across all age groups. Strategies for preventing and managing obesity are warranted to reduce the burden of obesity-related medical expenses.